History of the Electronic Magazine Educare of the National University of Costa Rica - Camacho Villalobos, María Elena (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
The aim of this work is to describe the history of the magazine Educare and its contributions to the academic and professional environment. Among its major achievements are: the improvement in its dissemination, visibility, the inclusion of international quality parameters and the income to recognized international catalogs. The magazine projects the formulation of a strategic plan to increase visibility, scope, social, professional and academic impact.